(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate the relationship between quality of sleep (QoS) and demographic, clinical, and psychosocial factors in kidney transplant recipients. Materials and Methods: We examined sixty-four kidney transplant recipients (26 female, 38 male). Clinical, demographic, and biochemical parameters were analyzed. The QoS was evaluated using Pittsburgh Sleep Quality Index (PSQI), health-related quality of life (HRQoL) with SF-36 Health Survey and depressive symptoms with Beck’s Depression Inventory (BDI). Results: A comparison of good and poor QoS (PSQI ≤ 5, PSQI > 5, respectively) groups showed a significant difference only in BDI scores (p 0.001). There was no statistically significant difference regarding urea, creatinine, ferritin, albumin, and other laboratory parameters. Thirty-six of the 46 patients (80%) in the good QoS group were married, while 10 of 19 patients (52%) in the poor QoS group were single. Married individuals had significantly better QoS (p=0.026). A comparison of the domains of the HRQoL survey showed significantly better “physical function” in those with good QoS than those with poor QoS (51 ± 6 and 47 ± 8, respectively; p 0.017). Conclusion: Patients with poor QoS had worse HRQoL. Routine screening of depressive symptoms, which may be manageable is required for improving QoS and HRQoL in these patients.